TO COMPARE THE EFFICACY OF INTERNAL SPHINCTEROTOMY WITH TOPICAL 0.2% GLYCERYL TRINITRATE OINTMENT AFTER HEMORRHOIDECTOMY FOR PAIN RELIEF: Topical 0.2% Glyceryl Trinitrate Ointment for Pain Relief - Ali, Adnan; Umair, Bilal; Ahmed, Maqsood; Perwaiz, Hafiz Khalid (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the efficacy of internal sphincterotomy with topical 0.2% glyceryl trinitrate ointment after hemorrhoidectomy for pain relief.Study Design: Randomized controlled trial. Place and Duration of Study: Department of surgery, Combined Military Hospital Rawalpindi.Material and Methods: Individual patients undergoing hemorrhoidectomy were randomized to either undergo internal sphincterotomy (Group A) or apply 0.2% glyceryl trinitrate (Group B). internal sphincter was divided up to dentate line through one of hemorrhoidectomy incisions. For 2nd group the first dose of 0.2% GTN ointment was applied at the end of hemorrhoidectomy. They were advised sitz bath 4 times daily and stool softener. Post operative pain was measured using visual analogue scale (VAS) on 1st, 2nd post op day and after a week and the average score was noted. VAS of pain far last visit was compared between the groups.Results:  Post operative pain was comparatively less in group A as compared to group B (p = 0.014).Conclusion: In patients undergoing hemorrhoidectomy, addition of surgical internal sphincterotomy results in lesser pain in the postoperative period as compared to those receiving topical application of 0.2% glyceryltrinitrate ointment.